Prevalência e fatores de risco para leishmaniose visceral em cães de Juatuba, Minas Gerais, 2010 - Luiz Felipe Nunes Menezes Borges (2011)
The purpose of this study was to estimate prevalence of canine Visceral Leishmaniasis (VL) and the occurrence of risk factors in Juatuba city, in 2010. A cross sectional study was carried out by venipuncture of 957 dogs randomly selected, followed by a half-structured questionnaire to their owners and the geographic punctuation of its residences. For canine survey, we used the enzyme-linked immunosorbent assay (ELISA) and the indirect immunofluorescence assay (IFA), according to what is established by the Ministry of Health (MS). The VL prevalence was estimated at 11.01%, being considered high. The infection was distributed in 70.6% of the 36 districts of the city, which presented epidemiological characteristics for maintenance of the disease. Three clusters were found and the risk of acquiring VL were 2.80 times higher in the primary. Juatuba was characterized by a population of low income and schooling level. The variables "presence of cattle," "large dog", "syntomatic dog ", and "biweekly cleaning peridomiciliar" were identified as risk factors (p 0.05) for VL. The variables "death of dogs infected with VL in the house", "vaccination against VL", "serologic testing for the disease" and "dog from Satellite district" also showed significant differences related to cases of VL, probably due to fact that the respondents have already had a previous contact with the disease. It was found that the interviewed people have poor knowledge about VL, and usually confuse it with other diseases. Most respondents did not practice preventive or control measures of the disease, or when held, they were few and nonspecific. Knowing about VL increases the chances of implementation of preventive measures directed to the individual, dog and environment. Studies involving health education for the entire population are needed to disseminate knowledge and to practice prevention and control activities in order to prevent further spread of the disease among dogs and the occurrence of human cases in the region.